BETAKAROTEN, ATIOKSIDAN DAN MUTU HEDONIK MINUMAN INSTAN LABU KUNING (Cucurbita moschata Dutch) BERDASARKANKONSENTRASI MALTODEKSTRIN - Dista Ferri Chahya Ningtias; Agus Suyanto; Nurhidajah Nurhidajah (Universitas Muhammadiyah Semarang, 2017)
ABSTRACT Pumpkin is one kind of gourd that populer in Indonesia which usually maked for compote (kolak) or just boiled it. However, pumpkin can be processed being an instant drink which dissolves easily in a water and have a long shelf life because the water content is low. The processing of pumpkin into instant drink needed a required fillers intended to inhibit the damage during a boiling. One of required filler usually used in the process of making an instant drink is maltodextrin. The general purpose of this research to determine of chemical characteristics, antiocsidative and hedonic quality of pumpkin instant drink by a subtitution of maltodextrin. The method of this research used a various experiments using completely randomized design (RAL) monofaktorial used a concentration factor of maltodextrin 0%, 1%, 2%, 3% and 4%. The product was analyzed chemical characteristics, antiocsidative and hedonic quality. Chemical characteristics and antioksidant’s data was analyzed by statistical methods ANOVA followed by a further test of LSD whereas the hedonic quality test results were analyzed using Friedman test and Wilcoxon test. Statistical analysis showed an influence from the concentration of maltodextrin against the chemical characteristics and hedonic quality in each of treatment but no influenced against the antiocsidative activity. The addition of 4% maltodextrin concentration resulted the best hedonic quality. Key Word : pumpkin, maltodextrin, beta caroten, antiocsidative, hedonic quality.